2020
DOI: 10.3390/w12041092
|View full text |Cite
|
Sign up to set email alerts
|

Lag Times as Indicators of Hydrological Mechanisms Responsible for NO3-N Flushing in a Forested Headwater Catchment

Abstract: Understanding the temporal variability of the nutrient transport from catchments is essential for planning nutrient loss reduction measures related to land use and climate change. Moreover, observations and analysis of nutrient dynamics in streams draining undisturbed catchments are known to represent a reference point by which human-influenced catchments can be compared. In this paper, temporal dynamics of nitrate-nitrogen (NO3-N) flux are investigated on an event basis by analysing observed lag times between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
1
0
2
Order By: Relevance
“…Na porečju je bila v okviru projekta SedAlp (2012SedAlp ( -2015 nameščena merska oprema za spremljanje količine, trajanja in lastnosti padavin, iznosa sedimentov in hidroloških razmer (Bezak et al, 2013). V letih 2018 in 2019 smo mersko mrežo posodobili z opremo za časovno zvezno spremljanje koncentracij NO3-N in vlažnosti tal (Sapač et al, 2020). V prispevku smo uporabili podatke meritev iz obdobja april 2018-april 2020.…”
Section: Podatkiunclassified
See 1 more Smart Citation
“…Na porečju je bila v okviru projekta SedAlp (2012SedAlp ( -2015 nameščena merska oprema za spremljanje količine, trajanja in lastnosti padavin, iznosa sedimentov in hidroloških razmer (Bezak et al, 2013). V letih 2018 in 2019 smo mersko mrežo posodobili z opremo za časovno zvezno spremljanje koncentracij NO3-N in vlažnosti tal (Sapač et al, 2020). V prispevku smo uporabili podatke meritev iz obdobja april 2018-april 2020.…”
Section: Podatkiunclassified
“…Osenčeni dogodki so iz obdobja vegetacije, ostali dogodki pa iz obdobja mirovanja. Ne glede na to, da z vidika režimov iznosa snovi s porečja sezonskost ni bila eksplicitno zaznana, pa je študija časov zakasnitve pretoka in iznosa snovi (Sapač et al, 2020) pokazala, da so časi zakasnitve v obdobju vegetacije oziroma v spomladanskopoletnem obdobju krajši kot v obdobju mirovanja oziroma jesensko-zimskem obdobju. Slednje potrjuje domnevo o vplivu sezonske raznolikosti padavin na oblikovanje hidrogramov odtoka in posledično na časovno dinamiko koncentracij NO3-N v vodotoku.…”
Section: Kategorizacija Dogodkov Glede Na Obdobjeunclassified
“…Numerous investigations have focused on the hydrologic response of catchments to particular rainfall occurrence, such as those by Pavlin et al (2021), Saffarpour et al (2016), andDetty &McGuire (2010), or have reported on the impact of rainfall characteristics on runoff quantity and quality, as seen in studies by Sapač et al (2020), Lintern et al (2018), andMacrae et al (2010). However, there are existing knowledge gaps regarding the relationships between hydrological responses, various rainfall events, and the reasons for variations in nutrient loads, particularly in pastoral catchments that contribute to lake inflows (Levine et al, 2021;Abell et al, 2013;Menneer et al, 2004).…”
Section: Introductionmentioning
confidence: 99%